Employer Resistance to Works Councils: Evidence from Surveys amongst Trade Unions. Issue 3 (2nd July 2020) - Behrens, Martin; Dribbusch, Heiner
Abstract : Employer resistance to works councils is not a phenomenon that has been closely associated with German labour relations. While classic studies characterise the 'German model' in terms of social partnership, more recent accounts seem to observe a 'dualisation' if not liberalisation of German labour relations. In somewhat of a contradiction to the 'social partnership' perspective, we find that incidents of employers' hostility towards the establishment of works councils are widespread. Based on data provided by the WSI Survey of paid union representatives (2012, 2015), we find that employers disrupt every sixth attempt to establish a works council. Among the measures taken by employers, the most common strategy is to intimidate works council candidates. Furthermore, we show that employers' hostility to works councils is evenly distributed between manufacturing (core) and private services (periphery), which suggests that the transformation of the 'German model' over the past decade follows a more nuanced path than suggested by accounts of dualisation. In contrast to the liberalisation hypothesis, our results also indicate that rather than affecting establishments across the board, attempts by employers to obstruct employees' participation rights are focused on a certain type of establishment: medium-sized and owner-managed firms.